Electrolyte additive, electrolyte, electrode assembly, battery, and electric device

By using a combination of trimethyl fluorosilane and alkenyl silane in the lithium-ion battery electrolyte, a low-impedance interface film is formed, which solves the problem of short battery cycle life caused by side reactions of the electrolyte at the cathode and anode interface, and improves the battery Electrochemical performance and fast charging performance.

CN119315105APending Publication Date: 2025-01-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310860597.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The side reaction of the electrolyte of existing lithium-ion batteries at the cathode and anode interface results in a short battery cycle life and poor electrochemical performance.

Method used

Trimethyl fluorosilane and alkenyl silane are used as electrolyte additives. Trimethyl fluorosilane is preferred to reduce at the anode interface to form a passivation film, inhibiting the reduction reaction of alkenyl silane, and alkenyl silane oxidizes the film at the cathode interface to form a low-level film. Impedance interface mask.

Benefits of technology

It improves the cycle life and fast charging performance of the battery, reduces the overall impedance of the battery, and improves the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315105A_ABST
    Figure CN119315105A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrolytes, in particular to an additive for an electrolyte, the electrolyte, an electrode assembly, a battery and an electric device. And the additive for the electrolyte comprises trimethylfluorosilane and alkenyl silane. According to the preparation method, the trimethylfluorosilane is preferentially reduced on the anode interface to form a passive film, so that the reduction of the alkenyl silane on the anode interface is inhibited, the alkenyl silane is favorably oxidized to form a film on the cathode interface, the film forming impedance of the alkenyl silane on the cathode interface is smaller than that of the alkenyl silane on the anode interface, and the cycle performance of the battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolytes, and in particular to an electrolyte additive, an electrolyte, an electrode assembly, a battery and an electrical device. Background Art

[0002] Secondary batteries such as lithium-ion batteries have attracted much attention due to their high specific energy, long cycle life, and low self-discharge. Currently, lithium-ion batteries have been used in all aspects of daily life such as cameras, laptops, electric vehicles, etc.

[0003] With the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention.

[0004] The electrolyte is an important component of secondary batteries. The electrolyte determines the composition and structure of the two-phase interface film on the electrode surface, and has an important influence on the structural stability and cycle life of the secondary battery electrode.

[0005] Improving the cycle life of batteries has always been the pursuit of the industry, but due to the side reactions of the electrolyte at the anode and cathode interfaces, the overall performance of the battery cell is poor. Summary of the invention

[0006] The main purpose of the present invention is to provide an electrolyte additive, aiming at improving the cycle performance of the battery.

[0007] To achieve the above object, the present invention provides an electrolyte additive, which includes trimethylfluorosilane and alkenylsilane.

[0008] As an electrolyte additive, vinyl silane can form a film at the cathode interface and the anode interface to improve the interface stability. Considering that the vinyl silane structure includes double bonds, it is reduced at the anode and has a large film formation impedance, which affects the deintercalation of ions at the anode interface and is not conducive to improving the battery power performance.

[0009] In order to solve the above problems, the present application adopts trimethylfluorosilane with a smaller molecular structure, which is easier to adsorb on the anode interface and preferentially reduced at the anode interface (trimethylfluorosilane structure contains Si-F structure, which is more conducive to reduction at the anode to form a SEI film rich in silicon and fluorine), forming a passivation film, thereby inhibiting the reduction of alkenylsilane at the anode interface, helping to oxidize alkenylsilane to form a film at the cathode interface, and the impedance of alkenylsilane film formation at the cathode interface is smaller than the impedance of its film formation at the anode, thereby improving the cycle performance of the battery.

[0010] It can also be understood that reducing battery impedance can also improve the fast charging performance of the battery.

[0011] Optionally, the mass ratio of the alkenyl silane to the trimethylfluorosilane is 1:(0.2 to 20), preferably, 1:(0.5 to 15).

[0012] When the alkenylsilane and trimethylfluorosilane in the electrolyte satisfy the above relationship, not only can a good interface film be formed at the anode and cathode interface, but the film formation impedance is also low, which helps to improve the cycle life.

[0013] That is, when the alkenylsilane and trimethylfluorosilane in the electrolyte satisfy the above relationship, trimethylfluorosilane is preferentially reduced at the anode interface to form a passivation film, thereby inhibiting the reduction of alkenylsilane at the anode interface, which helps to oxidize alkenylsilane to form a film at the cathode interface. The impedance of alkenylsilane film formation at the cathode interface is smaller than that at the anode interface, thereby not only forming a good interface film at the anode interface, but also having a low film formation impedance.

[0014] Optionally, the alkenyl silane includes at least one of tetravinylsilane, ethyltrivinylsilane, methyltrivinylsilane, diethyldivinylsilane, methylethyldivinylsilane, triethylvinylsilane, trimethylvinylsilane and diethylmethylvinylsilane.

[0015] The alkenyl silanes in the present application include, but are not limited to, at least one of tetravinylsilane, ethyltrivinylsilane, methyltrivinylsilane, diethyldivinylsilane, methylethyldivinylsilane, triethylvinylsilane, trimethylvinylsilane and diethylmethylvinylsilane.

[0016] It is understandable that, considering that trimethylfluorosilane is gaseous, has low solubility, and is not easy to form a film at the anode interface, in order to improve this problem, a substance for producing trimethylfluorosilane can be added to the electrolyte, so that the substance reacts in the electrolyte to produce trimethylfluorosilane, so that trimethylfluorosilane exists in the electrolyte as a product, so that its solubility and dispersibility in the electrolyte are better, which is conducive to its film formation. It is understandable that the substance used to produce trimethylfluorosilane in the electrolyte includes tris (trimethylsilane) borate, tris (trimethylsilyl) phosphate, trimethyl trimethyl silane, trifluoro trimethyl silane, hexamethyl disilazane, etc. For example, the fluorine in LiPF6 in the electrolyte attacks tris (trimethylsilane) borate and tris (trimethylsilane) phosphate, and reacts during battery formation (battery temperature is 35°C-60°C) to generate trimethylfluorosilane, or hexamethyl disilazane directly reacts with HF or fluorine-containing compounds to obtain trimethylfluorosilane.

[0017] Optionally, the present application also provides an electrolyte, the electrolyte comprising the electrolyte additive as described above.

[0018] Optionally, the mass percentage of the alkenyl silane to the total mass of the electrolyte is W1, and the mass percentage of the trimethylfluorosilane to the total mass of the electrolyte is W2, then W1 / W2=1:(0.2 to 20), preferably, W1 / W2=1:(0.5 to 15).

[0019] When the alkenylsilane and alkylsilicon in the electrolyte satisfy the above relationship, not only can a good interface film be formed at the anode and cathode interface, but the film formation resistance is also low.

[0020] Optionally, 0.1%≤W1≤5%, preferably, 0.3%≤W1≤3%;

[0021] And / or, 0.05%≤W2≤3%, preferably, 0.1≤W2≤2%.

[0022] Considering that when the mass percentage of alkenylsilane in the electrolyte is too low, the interface formed at the cathode is unstable and easily broken. When the mass percentage of alkenylsilane is too large, it is difficult to achieve further protection, but it will significantly increase the cost. For this reason, considering the stability of alkenylsilane film formation at the cathode interface and the added cost, 0.1% ≤ W1 ≤ 5%, preferably 0.3% ≤ W1 ≤ 3%.

[0023] Considering that the mass percentage of trimethylfluorosilane in the electrolyte is too low, it is difficult to achieve the beneficial effect of film formation at the anode interface. When the mass percentage is too high, it will deteriorate the formation and gas production, which is not conducive to the production of batteries in terms of technology. Therefore, considering the film formation of trimethylfluorosilane at the anode interface and the risk of deteriorating the formation and gas production, 0.05%≤W2≤3% is selected, preferably 0.1≤W2≤2%.

[0024] Optionally, the electrolyte further comprises a lithium salt, and the lithium salt comprises at least one of LiPF6, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl(perfluorobutylsulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide;

[0025] And / or, the electrolyte further includes a solvent, and the solvent includes at least one of ethylene carbonate, dimethyl carbonate, propylene carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, r-butyrolactone, fluoroethylene carbonate, diethyl carbonate, ethyl acetate, methyl acetate, methyl propionate, ethyl propionate, and propyl propionate.

[0026] The electrolyte in the present application also includes a lithium salt, which includes but is not limited to at least one of LiPF6, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl (perfluorobutylsulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0027] The electrolyte in the present application also includes a solvent, and the solvent includes but is not limited to at least one of ethylene carbonate, dimethyl carbonate, propylene carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, r-butyrolactone, fluoroethylene carbonate, diethyl carbonate, ethyl acetate, methyl acetate, methyl propionate, ethyl propionate, and propyl propionate.

[0028] Optionally, the present application also provides an electrode assembly, which includes a positive electrode plate, a negative electrode plate and the electrolyte as described.

[0029] Optionally, the positive electrode plate includes a positive electrode material, and the positive electrode material is doped with a doping element.

[0030] In order to further improve the service life of the battery, elements are usually doped into the positive electrode material so that the positive electrode material maintains structural stability and improves structural collapse during the process of ion insertion and extraction.

[0031] However, the doping elements in the positive electrode can be easily dissolved from the positive electrode structure under the action of HF in the electrolyte, causing the positive electrode structure to be destroyed, thereby affecting the service life of the battery.

[0032] In order to improve the above problems, the present application adopts alkenyl silane for cathode oxidation to form a good CEI film, which can block the contact between the doping elements and HF to a certain extent and alleviate the dissolution of transition metal ions.

[0033] Optionally, the mass percentage of the doping element to the mass of the positive electrode material is W3, the mass percentage of the alkenylsilane to the total mass of the electrolyte is W1, satisfying 1≤W1 / W3≤20, preferably, 1≤W1 / W3≤18.

[0034] It can be understood that when the mass percentage of the doping element in the positive electrode to the mass percentage of the positive electrode material and the mass percentage of the alkenylsilane to the total mass of the electrolyte meet the above relationship, a better effect can be achieved. When the ratio of the mass percentage of the doping element in the positive electrode material to the mass percentage of the alkenylsilane in the electrolyte is low, the dissolution of the doping element cannot be effectively suppressed due to the low content of the alkenylsilane. When the ratio of the mass percentage of the doping element in the positive electrode material to the mass percentage of the alkenylsilane in the electrolyte is high, the alkenylsilane content is too high, the positive electrode film formation impedance is too large, and the polarization increases, resulting in the battery fast charging reaching the cut-off potential during charging, and the released capacity is reduced, that is, the polarization increases, the battery reaches the cut-off voltage in advance, resulting in the battery not being fully charged, thereby reducing the released capacity.

[0035] Optionally, the mass percentage of the mass of the doping element to the mass of the positive electrode material is W3, satisfying 0.005%≤W3≤0.5%, preferably, 0.005%≤W3≤0.3%.

[0036] Considering that when the mass of the doped elements in the positive electrode material accounts for a low percentage of the mass of the positive electrode material, it is difficult to stabilize the positive electrode structure; when the mass of the doped elements in the positive electrode material accounts for a high percentage of the mass of the positive electrode material, it is difficult to further stabilize the positive electrode structure, but it will reduce the energy density of the battery.

[0037] Optionally, the doping element includes at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al.

[0038] The doping elements in the positive electrode material in the present application include but are not limited to at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al.

[0039] Optionally, the positive electrode material includes Li x Ni a Co b Mn c M d O 2-e , M includes at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al, 0.65≤a≤0.98, 0≤b≤0.3, 0.02≤c≤0.3, 0≤d≤0.3, a+b+c+d=1, 0.1≤x≤1.3, 0≤e≤1.9.

[0040] The cathode materials in this application include but are not limited to Li x Ni a Co b Mn c M d O 2-e , M includes at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al, 0.65≤a≤0.98, 0≤b≤0.3, 0.02≤c≤0.3, 0≤d≤0.3, a+b+c+d=1, 0.1≤x≤1.3, 0≤e≤1.9.

[0041] The present application also provides a battery, which includes the electrode assembly as described.

[0042] The present application also provides an electrical device, which includes the battery as described above.

[0043] The electrolyte additives of the present application include trimethyl fluorosilane and alkenyl silane. The present application uses trimethyl fluorosilane to be preferentially reduced at the anode interface to form a passivation film, thereby inhibiting the reduction of alkenyl silane at the anode interface, and helping to oxidize alkenyl silane to form a film at the cathode interface. The impedance of alkenyl silane film formation at the cathode interface is lower than that of alkenyl silane film formation at the anode interface, thereby improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0045] Figure 1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0046] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;

[0047] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0048] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0049] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0050] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0051] Description of Figure Numbers:

[0052] Label name Label name 1 Battery Pack 5 Secondary battery 2 Upper box 51 case 3 Lower box 52 Electrode assembly 4 Battery Module 53 Top cover assembly

[0053] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0054] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Hereinafter, the embodiments of the electrolyte additive, electrolyte, electrode assembly, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0056] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0057] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0058] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0059] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0060] With the rapid growth of portable electronic devices and electric vehicles, the demand for power batteries is also growing. Among them, the electrochemical performance of batteries is also attracting more and more attention.

[0061] The electrolyte is an important component of secondary batteries. The electrolyte determines the composition and structure of the two-phase interface film on the electrode surface, and has an important influence on the structural stability and cycle life of the secondary battery electrode.

[0062] Improving the cycle life of batteries has always been the pursuit of the industry, but due to the side reactions of the electrolyte at the anode and cathode interfaces, the overall performance of the battery cell is poor.

[0063] In order to improve the side reactions of the electrolyte at the anode-cathode interface, a film-forming substance may be added to the electrolyte to help form a film at the anode-cathode interface, thereby reducing the side reactions.

[0064] For example, by adding tetravinylsilane to the electrolyte, the characteristic of tetravinylsilane participating in film formation can be utilized to reduce side reactions.

[0065] Although tetravinylsilane has good film-forming properties, due to the double bonds in its structure, the film-forming resistance is large during anode reduction, which seriously affects the intercalation and deintercalation of ions in secondary batteries (for example, secondary batteries include lithium-ion batteries) at the anode interface, which is not conducive to improving the power performance of the battery.

[0066] In order to improve the above problems, the present invention proposes an electrolyte additive, which includes trimethylfluorosilane and alkenylsilane.

[0067] Alkenyl silane includes a silicon atom and an alkenyl functional group connected to the silicon atom in its structure.

[0068] Specifically, alkenylsilane can form a film at the cathode interface and the anode interface to improve the interface stability. Considering that the alkenylsilane structure includes double bonds, it is reduced at the anode and has a large film formation impedance, which affects the deintercalation of ions at the anode interface and is not conducive to improving the battery power performance.

[0069] The electrolyte additive of the present application includes trimethylfluorosilane, which has a smaller molecular structure and is more easily adsorbed on the anode interface, and is preferentially reduced at the anode interface (trimethylfluorosilane contains Si-F structure, which is more conducive to reduction at the anode to form a SEI film rich in silicon and fluorine), forming a passivation film, thereby inhibiting the reduction of alkenylsilane at the anode interface, and helping to make alkenylsilane oxidized to form a film at the cathode interface. The impedance of alkenylsilane film formation at the cathode interface is less than its impedance at the anode film formation, thereby improving the battery's cycle performance. It can also be understood that the reduction of battery impedance can also improve the fast charging performance of the battery.

[0070] It is understandable that, taking tetravinylsilane as an example, tetravinylsilane contains four double bonds, which are very easy to undergo reduction reaction on the anode side to generate polymers with large impedance. However, at the cathode, the four double bonds are oxidized, and the electrolyte participates in the reaction to generate CO2, forming a CEI film containing silicon, so the film formation impedance is small.

[0071] In one embodiment, the mass ratio of the alkenyl silane to the trimethylfluorosilane is 1:(0.2 to 20), preferably, 1:(0.5 to 15).

[0072] When the alkenylsilane and trimethylfluorosilane in the electrolyte satisfy the above relationship, not only can a good interface film be formed at the anode and cathode interface, but the film formation impedance is also low.

[0073] That is, when the alkenylsilane and trimethylfluorosilane in the electrolyte satisfy the above relationship, trimethylfluorosilane is preferentially reduced at the anode interface to form a passivation film, thereby inhibiting the reduction of alkenylsilane at the anode interface, which helps to oxidize alkenylsilane to form a film at the cathode interface. The impedance of alkenylsilane film formation at the cathode interface is smaller than that at the anode interface, thereby not only forming a good interface film at the anode interface, but also having a low film formation impedance.

[0074] In one embodiment, the alkenyl silane includes at least one of tetravinyl silane, ethyltrivinyl silane, methyltrivinyl silane, diethyldivinyl silane, methylethyldivinyl silane, triethylvinyl silane, trimethylvinyl silane, and diethylmethylvinyl silane.

[0075] The alkenyl silanes in the present application include, but are not limited to, at least one of tetravinylsilane, ethyltrivinylsilane, methyltrivinylsilane, diethyldivinylsilane, methylethyldivinylsilane, triethylvinylsilane, trimethylvinylsilane and diethylmethylvinylsilane.

[0076] It is understandable that, considering that trimethylfluorosilane is gaseous, has low solubility, and is not easy to form a film at the anode interface, in order to improve this problem, a substance for producing trimethylfluorosilane can be added to the electrolyte, so that the substance reacts in the electrolyte to produce trimethylfluorosilane, so that trimethylfluorosilane exists in the electrolyte as a product, so that its solubility and dispersibility in the electrolyte are better, which is conducive to its film formation. It is understandable that the substance used to produce trimethylfluorosilane in the electrolyte includes tris (trimethylsilane) borate, tris (trimethylsilyl) phosphate, trimethyl trimethyl silane, trifluoro trimethyl silane, hexamethyl disilazane, etc. For example, the fluorine in LiPF6 in the electrolyte attacks tris (trimethylsilane) borate and tris (trimethylsilane) phosphate, and reacts during battery formation (battery temperature is 35°C-60°C) to generate trimethylfluorosilane, or hexamethyl disilazane directly reacts with HF or fluorine-containing compounds to obtain trimethylfluorosilane.

[0077] In one embodiment, the present application further provides an electrolyte, wherein the electrolyte includes the electrolyte additive as described above.

[0078] In one embodiment, the mass percentage of the alkenyl silane to the total mass of the electrolyte is W1, and the mass percentage of the trimethylfluorosilane to the total mass of the electrolyte is W2, then W1 / W2=1:(0.2 to 20), preferably, W1 / W2=1:(0.5 to 15).

[0079] Define the mass of alkenylsilane as m1, and the total mass of the electrolyte as M. Then the mass percentage of alkenylsilane to the total mass of the electrolyte satisfies W1=(m1 / M)×100%.

[0080] When the alkenylsilane and trimethylfluorosilane in the electrolyte satisfy the above relationship, not only can a good interface film be formed at the anode and cathode interface, but the film formation impedance is also low.

[0081] In the above 1: (0.2 to 20), the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1: 0.2, 1: 0.5, 1: 1, 1: 2, 1: 5, 1: 8, 1: 10, 1: 12, 1: 14, 1: 16, 1: 18, 1: 20, etc., as well as the range values ​​between any two of the above point values.

[0082] In one embodiment, 0.1%≤W1≤5%, preferably, 0.3%≤W1≤3%; and / or, 0.05%≤W2≤3%, preferably, 0.1≤W2≤2%.

[0083] Considering that when the mass percentage of alkenylsilane in the electrolyte is too low, the interface formed at the cathode is unstable and easily broken. When the mass percentage of alkenylsilane is too large, it is difficult to achieve further protection, but the cost will be significantly increased. For this reason, considering the stability of the film formed by alkenylsilane at the cathode interface and the added cost, 0.1% ≤ W1 ≤ 5% is selected, preferably 0.3% ≤ W1 ≤ 3%.

[0084] Furthermore, when alkenylsilane is a substance with a low flash point, its mass percentage in the electrolyte should not be too large. For example, when alkenylsilane is tetravinylsilane, it has a low flash point and is prone to catching fire when static sparks are generated when the battery is damaged.

[0085] Considering that the mass percentage of trimethylfluorosilane in the electrolyte is too low, it is difficult to achieve the beneficial effect of film formation at the anode interface. When the mass percentage is too high, it will deteriorate the formation and gas production, which is not conducive to the production of batteries in terms of technology. Therefore, considering the film formation of trimethylfluorosilane at the anode interface and the risk of deteriorating the formation and gas production, 0.05%≤W2≤3% is selected, preferably 0.1≤W2≤2%.

[0086] In the above 0.1%≤W1≤5%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.6%, 2.8%, 3%, 3.6%, 3.8%, 4%, 4.6%, 4.8%, 5%, etc., and the range value between any two of the above point values.

[0087] In the above 0.05%≤W2≤3%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.05%, 0.06%, 0.08%, 0.09%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.6%, 2.8%, 3%, etc., and the range values ​​between any two of the above point values.

[0088] In one embodiment, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of LiPF6, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl (perfluorobutylsulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide; and / or, the electrolyte further includes a solvent, and the solvent includes at least one of ethylene carbonate, dimethyl carbonate, propylene carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, r-butyrolactone, fluoroethylene carbonate, diethyl carbonate, ethyl acetate, methyl acetate, methyl propionate, ethyl propionate, and propyl propionate.

[0089] The electrolyte in the present application also includes a lithium salt, which includes but is not limited to at least one of LiPF6, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl (perfluorobutylsulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0090] The electrolyte in the present application also includes a solvent, and the solvent includes but is not limited to at least one of ethylene carbonate, dimethyl carbonate, propylene carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, r-butyrolactone, fluoroethylene carbonate, diethyl carbonate, ethyl acetate, methyl acetate, methyl propionate, ethyl propionate, and propyl propionate.

[0091] In one embodiment, the present application also provides an electrode assembly, which includes a positive electrode plate, a negative electrode plate and the electrolyte as described above.

[0092] In one embodiment, the positive electrode plate includes a positive electrode material, and the positive electrode material is doped with a doping element.

[0093] In order to further improve the service life of the battery, elements are usually doped into the positive electrode material so that the positive electrode material maintains structural stability and improves structural collapse during the process of ion insertion and extraction.

[0094] However, the doping elements in the positive electrode can be easily dissolved from the positive electrode structure under the action of HF in the electrolyte, causing the positive electrode structure to be destroyed, thereby affecting the service life of the battery.

[0095] In order to improve the above problems, the present application adopts alkenyl silane for cathode oxidation to form a good CEI film, which can block the contact between the doping elements and HF to a certain extent and alleviate the dissolution of transition metal ions.

[0096] It is understandable that trimethyl fluorosilane inhibits tetravinyl silane from forming a film at the anode, so that tetravinyl silane forms a film at the cathode. Otherwise, the reduction reaction of tetravinyl silane at the anode not only has a large film resistance, but also is mostly consumed. The remaining additive forms less film at the cathode and it is difficult to block the dissolution of doped elements in the cathode material. The present application utilizes trimethyl fluorosilane to inhibit tetravinyl silane from forming a film at the anode, so that even at a low concentration of tetravinyl silane, there is enough tetravinyl silane to form a film at the cathode, blocking the contact between the doped elements in the cathode material and HF, which has the effect of alleviating the dissolution of transition metal ions. And the addition of low concentrations of tetravinyl silane can reduce costs, that is, through the combination of trimethyl fluorosilane and tetravinyl silane in the present application, a smaller amount of additives can be used to achieve improved battery performance, that is, while improving battery performance, the cost of additive investment can be saved.

[0097] In one embodiment, the mass percentage of the doping element to the mass of the positive electrode material is W3, the mass percentage of the alkenyl silane to the total mass of the electrolyte is W1, satisfying 1≤W1 / W3≤20, preferably, 1≤W1 / W3≤18.

[0098] It can be understood that when the mass percentage of the doping element in the positive electrode to the mass percentage of the positive electrode material and the mass percentage of the alkenylsilane to the total mass of the electrolyte meet the above relationship, a better effect can be achieved. When the ratio of the mass percentage of the doping element in the positive electrode material to the mass percentage of the alkenylsilane in the electrolyte is low, the dissolution of the doping element cannot be effectively suppressed due to the low content of the alkenylsilane. When the ratio of the mass percentage of the doping element in the positive electrode material to the mass percentage of the alkenylsilane in the electrolyte is high, the alkenylsilane content is too high, the positive electrode film formation impedance is too large, and the polarization increases, resulting in the battery fast charging reaching the cut-off potential during charging, and the released capacity is reduced, that is, the polarization increases, the battery reaches the cut-off voltage in advance, resulting in the battery not being fully charged, thereby reducing the released capacity.

[0099] In the above 1≤W1 / W3≤20, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1, 2, 5, 8, 10, 12, 15, 18, 20, etc., and the range values ​​between any two of the above point values.

[0100] In one embodiment, the mass percentage of the mass of the doping element to the mass of the positive electrode material is W3, which satisfies 0.005%≤W3≤0.5%, preferably, 0.005%≤W3≤0.3%.

[0101] Considering that when the mass percentage of the doping element in the positive electrode material is low, it is difficult to stabilize the positive electrode structure. When the mass percentage of the doping element in the positive electrode material is high, it is difficult to further stabilize the positive electrode structure, but it will reduce the energy density of the battery. To this end, the mass percentage of the doping element in the mass of the positive electrode material is W3, which satisfies 0.005%≤W3≤0.5%, preferably, 0.005%≤W3≤0.3%.

[0102] In the above 0.005%≤W3≤0.5%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.005%, 0.006%, 0.008%, 0.01%, 0.03%, 0.05%, 0.06%, 0.08%, 0.09%, 0.1%, 0.2%, 0.5%, etc., and the range value between any two of the above point values.

[0103] In one embodiment, the doping element includes at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al.

[0104] The doping elements in the positive electrode material in the present application include but are not limited to at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al.

[0105] In one embodiment, the positive electrode material includes Li x Ni a Co b Mn c M d O 2-e , M includes at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al, 0.65≤a≤0.98, 0≤b≤0.3, 0.02≤c≤0.3, 0≤d≤0.3, a+b+c+d=1, 0.1≤x≤1.3, 0≤e≤1.9.

[0106] The cathode materials in this application include but are not limited to Li x Ni a Co b Mn c M d O 2-e , M includes at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al, 0.65≤a≤0.98, 0≤b≤0.3, 0.02≤c≤0.3, 0≤d≤0.3, a+b+c+d=1, 0.1≤x≤1.3, 0≤e≤1.9.

[0107] In one embodiment, alkenyl silanes include tetravinylsilane and trimethylfluorosilane. Considering that tetravinylsilane can form a film at the cathode interface and the anode interface, improve the stability of the interface, and improve the cycle life, but its molecular structure contains four alkenyl groups, which is very easy to reduce at the anode interface, and the SEI film formed is thicker, which is not conducive to the transmission of lithium ions (this application does not limit the type of secondary battery, taking lithium secondary battery as an example) at the anode interface, and thus is not conducive to the improvement of the fast charging performance of the battery. The electrolyte additive includes trimethylfluorosilane, which is preferentially reduced at the anode to form a thin and dense passivation film, thereby inhibiting the reduction of tetravinylsilane at the anode, which can improve the fast charging performance of the battery. The combined use of the two can improve the fast charging performance of the battery cell while taking into account the cycle life.

[0108] In order to further improve the service life of the battery, elements are usually doped in the positive electrode material so that the positive electrode material maintains structural stability during the lithium insertion and extraction process. However, the doping elements in the positive electrode material are easily dissolved from the positive electrode material structure under the action of HF in the electrolyte, so that the positive electrode structure is destroyed, thereby affecting the service life of the battery. In this application, tetravinylsilane is oxidized at the cathode to form a good CEI film, which can block the contact between the doping elements and HF to a certain extent, and play a role in alleviating the dissolution of transition metal ions. When the content of doping elements in the positive electrode material and the content of tetravinylsilane meet the above relationship, it can have a very good effect. In summary, when the content of doping elements in the positive electrode material, the content of tetravinylsilane in the electrolyte, and the content of trimethylfluorosilane meet the above relationship, a battery with excellent cycle life and fast charging performance can be obtained.

[0109] In one embodiment, the present application also provides a battery, which includes the electrode assembly as described above.

[0110] Since the electrode assembly adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0111] It is understandable that batteries include secondary batteries, battery modules, and battery packs.

[0112] In one embodiment, the present application further provides an electrical device, which includes the above-mentioned battery.

[0113] Since the battery adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0114] In addition, the battery (secondary battery, battery module, battery pack) and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0115] In one embodiment of the present application, a secondary battery is provided.

[0116] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The separator is the separator improved above in this application.

[0117] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.

[0118] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0119] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0120] In some embodiments, when the electrode assembly is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0121] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0122] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0123] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0124] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0125] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0126] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.

[0127] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0128] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0129] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0130] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0131] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0132] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0133] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0134] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0135] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0136] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0137] In some embodiments, the electrolyte may further include additives that can improve certain properties of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high or low temperature performance of the battery, etc.

[0138] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0139] In some embodiments, the material of the diaphragm can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The diaphragm can be a single-layer film or a multi-layer composite film, without particular limitation. When the diaphragm is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0140] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0141] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0142] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0143] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0144] In some embodiments, reference Figure 2, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the diaphragm can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0145] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0146] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0147] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0148] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0149] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0150] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0151] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0152] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0153] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0154] Example

[0155] Example 1

[0156] Preparation of electrolyte:

[0157] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), ethylene carbonate and ethyl methyl carbonate (3:7V / V) are mixed evenly in a certain ratio, and then an appropriate amount of LiPF6 is slowly added to the non-aqueous organic solvent. After the lithium salt is completely dissolved, a 1 mol / L electrolyte is obtained. Subsequently, an appropriate amount of tetravinylsilane and trimethylfluorosilane are added, and the electrolyte is obtained after stirring evenly.

[0158] Preparation of positive electrode active material: The precursor powder of the nickel-cobalt-manganese ternary positive electrode active material is mixed with a salt solution containing a doping element and subjected to a liquid phase diffusion reaction, and the doped precursor powder is obtained after drying. The salt solution of the doping element is a soluble metal solution containing the doping element (for example, its solute includes one of zinc sulfate, magnesium sulfate, aluminum chloride or zirconium nitrate, and its solvent is ethanol. In Example 1, the doping element is Zr, and the solute includes zirconium nitrate). The above solute and solvent are mixed to prepare a doping element salt solution, and then the ternary precursor powder is mixed with the doping element salt solution and subjected to a liquid phase diffusion reaction. The solid content percentage is 30% to 50% by weight (in Example 1, the solid content percentage is 40% by weight). The doping element is uniformly infiltrated into the voids of the nickel-cobalt-manganese ternary positive electrode active material through the solution in a liquid phase diffusion manner. The specific liquid phase diffusion reaction process conditions are as follows: the reaction temperature is 25°C to 40°C (in Example 1, the reaction temperature is 35°C), the reaction time is 30min to 90min (in Example 1, the reaction time is 60min), and the stirring speed is 15Hz to 45Hz (in Example 1, the stirring speed is 30Hz). The positive electrode active material is obtained. The parameters of the positive electrode active material and its chemical formula are shown in Table 1.

[0159] The prepared positive electrode active material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) are prepared into positive electrode slurry in N-methylpyrrolidone (NMP). The solid content in the positive electrode slurry is 50wt%, and the solid content of LiNi 0.5 Co 0.2 Mn 0.3 The mass ratio of O2, Super P, and PVDF is 8:1:1. The positive electrode slurry is coated on the current collector aluminum foil and dried at 85°C, then cold pressed, trimmed, cut, and striped, and then dried at 85°C under vacuum for 4 hours to make a positive electrode sheet.

[0160] Preparation of negative electrode:

[0161] Graphite as the negative electrode active material, a certain amount of silicon, conductive agent Super P, thickener CMC, and adhesive styrene butadiene rubber (SBR) are mixed evenly in deionized water to form a negative electrode slurry. The solid content in the negative electrode slurry is 30wt%, and the mass ratio of graphite, Super P, CMC and adhesive styrene butadiene rubber (SBR) in the solid components is 80:15:3:2. The negative electrode slurry is coated on the current collector copper foil and dried at 85°C, then cold pressed, trimmed, cut, and striped, and then dried at 120°C under vacuum conditions for 12 hours to form a negative electrode sheet.

[0162] Preparation of lithium-ion batteries:

[0163] A 16μm polyethylene film (PE) is used as a separator. The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrode sheets to isolate the positive and negative electrodes, and the bare battery cell is wound, and the pole ears are welded. The bare battery cell is placed in an outer package, and the prepared electrolyte is injected into the dried battery cell, and the lithium-ion battery is prepared by packaging, standing, forming, shaping, and capacity testing (the thickness of the soft-pack lithium-ion battery is 4.0mm, the width is 60mm, and the length is 140mm).

[0164] Example 2 to Example 14

[0165] On the basis of Example 1, the type of doping element in the positive electrode material, the mass percentage of the doping element in the positive electrode material W3, the mass percentage of tetravinylsilane in the electrolyte W1, the mass percentage of trimethylfluorosilane in the electrolyte W2, etc. are adjusted to obtain Examples 2 to 14 in Table 1.

[0166] Comparative Examples 1 to 4

[0167] Comparative Example 1 Based on Example 2, no tetravinylsilane was added to obtain Comparative Example 1 in Table 1.

[0168] Comparative Example 2 is based on Example 4, but without adding trimethylfluorosilane, to obtain Comparative Example 2 in Table 1.

[0169] Comparative Example 3 is based on Example 14, but tetravinylsilane is not added to obtain Comparative Example 3 in Table 1.

[0170] Comparative Example 4 is based on Example 14, except that trimethylfluorosilane is not added, and the mass percentage of tetravinylsilane in the electrolyte is adjusted to W1, to obtain Comparative Example 4 in Table 1.

[0171] Performance Testing

[0172] Lithium-ion battery cycle performance test:

[0173] The ambient temperature was adjusted to 25°C, the battery was charged to 4.35V at 1C, then charged to 0.05C at a constant voltage, left to stand for 10 minutes, and discharged to 2.8V at 1C. The discharge capacity was recorded as C0. 300 cycles were performed according to the above charge and discharge process. The discharge capacity at the 300th cls was C1. The cycle capacity retention rate of the battery = C0 / C1*100%

[0174] Power performance test of lithium-ion batteries:

[0175] The battery was discharged to 2.8V at 1C, then left to stand for 5 minutes, charged to 4.35V at 0.5C, charged to 0.05C at constant voltage, then discharged to 2.8C, and the discharge capacity was recorded as C. Then, it was charged to 4.35V at 0.5C, charged to 0.05C at constant voltage, and the battery was placed in a 25°C thermostat for 30 minutes, and the voltage at the end of the standstill was recorded. Then, it was continuously discharged at 4C for 30 seconds, and the voltage at the end of the discharge was recorded as V2. The battery's DCR (Direct Current Resistance) = (V1-V2) / I, I = 4C.

[0176] Table 1 List of Examples

[0177]

[0178]

[0179] Table 2 Performance list

[0180] serial number DCR Cycle life Example 1 13.0 94.3% Example 2 12.0 96.7% Example 3 14.0 95.3% Example 4 16.0 97.3% Example 5 19.0 91.2% Example 6 33.0 90.9% Example 7 15.0 97.8% Example 8 13.0 98.2% Example 9 17 97.1% Example 10 40.0 90.5% Embodiment 11 8.0 90.2% Example 12 10.0 98.7% Embodiment 13 10.0 99.3% Embodiment 14 43 89.9% Comparative Example 1 56.0 78.2% Comparative Example 2 50.0 80.2% Comparative Example 3 61 77.7% Comparative Example 4 54 78.4%

[0181] From the test results in Table 2, it can be understood that DCR (Direct Current Resistance) represents the DC resistance. Compared with the power performance and cycle performance obtained by the tests of Comparative Examples 1 to 4, the comprehensive performance of Examples 1 to 14 is improved. This indicates that adding alkenylsilane and alkyl silicon to the electrolyte can reduce the DC resistance of the battery, and the reduction of the DC resistance can improve the fast charging performance of the battery, thereby obtaining a battery with better cycle performance.

[0182] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. An electrolyte additive, characterized in that: The electrolyte additive includes trimethylfluorosilane and alkenylsilane.

2. The electrolyte additive according to claim 1, characterized in that The mass ratio of the alkenylsilane to the trimethylfluorosilane is 1:(0.2 to 20), preferably, 1:(0.5 to 15).

3. The electrolyte additive according to claim 1 or 2, characterized in that: The alkenyl silane includes at least one of tetravinylsilane, ethyltrivinylsilane, methyltrivinylsilane, diethyldivinylsilane, methylethyldivinylsilane, triethylvinylsilane, trimethylvinylsilane and diethylmethylvinylsilane.

4. An electrolyte, characterized in that: The electrolyte solution includes the electrolyte solution additive according to any one of claims 1 to 3.

5. The electrolyte according to claim 4, characterized in that The mass percentage of the alkenyl silane to the total mass of the electrolyte is W1, and the mass percentage of the trimethylfluorosilane to the total mass of the electrolyte is W2, then W1 / W2=1:(0.2 to 20), preferably, W1 / W2=1:(0.5 to 15).

6. The electrolyte according to claim 5, characterized in that 0.1%≤W1≤5%, preferably, 0.3%≤W1≤3%; And / or, 0.05%≤W2≤3%, preferably, 0.1≤W2≤2%.

7. The electrolyte according to any one of claims 4 to 6, characterized in that The electrolyte further includes a lithium salt, and the lithium salt includes at least one of LiPF6, lithium bis(fluorosulfonyl)imide, lithium fluorosulfonyl (perfluorobutylsulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide; And / or, the electrolyte further includes a solvent, and the solvent includes at least one of ethylene carbonate, dimethyl carbonate, propylene carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, r-butyrolactone, fluoroethylene carbonate, diethyl carbonate, ethyl acetate, methyl acetate, methyl propionate, ethyl propionate, and propyl propionate.

8. An electrode assembly, characterized in that: The electrode assembly comprises a positive electrode sheet, a negative electrode sheet and an electrolyte as claimed in any one of claims 4 to 7.

9. The electrode assembly according to claim 8, characterized in that The positive electrode plate includes a positive electrode material, and the positive electrode material is doped with a doping element.

10. The electrode assembly according to claim 9, characterized in that The mass percentage of the doping element to the mass percentage of the positive electrode material is W3, and the mass percentage of the alkenylsilane to the total mass of the electrolyte is W1, satisfying 1≤W1 / W3≤20, preferably, 1≤W1 / W3≤18.

11. The electrode assembly according to claim 9 or 10, characterized in that: The mass percentage of the doping element to the mass percentage of the positive electrode material is W3, which satisfies 0.005%≤W3≤0.5%, preferably, 0.005%≤W3≤0.3%.

12. The electrode assembly according to any one of claims 9 to 11, characterized in that: The doping element includes at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al.

13. The electrode assembly according to any one of claims 9 to 12, characterized in that: The positive electrode material includes Li x Ni a Co b Mn c M d O 2-e , M includes at least one of W, Cu, Fe, Mg, V, B, Cr, Ti, Zr, Zn and Al, 0.65≤a≤0.98, 0≤b≤0.3, 0.02≤c≤0.3, 0≤d≤0.3, a+b+c+d=1, 0.1≤x≤1.3, 0≤e≤1.

9.

14. A battery, characterized in that: The battery comprises the electrode assembly according to any one of claims 8 to 13.

15. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 14.

Citation Information

Cited By

  • Battery cell, battery device and electric device

    CN121355384A